Adsorption Characteristics of an AlGaN/GaN Heterojunction on Potassium Ions - Yan Dong; Mengmeng Li; Yanli Liu; Jianming Lei; Haineng Bai; Yanmei Sun; Dunjun Chen; Dongjie Zhu; Rigao Wang; Yi Sun (Molecules, 2025)
Slight changes in potassium levels can affect health. Therefore, rapid, reliable, and quantitative determination of potassium ion content is important for medical diagnosis. AlGaN, as a semiconductor material with good biocompatibility, has many advantages in the development of new potassium ion sensors. Understanding the adsorption behavior of a specific ion on the AlGaN surface and the eventual effect on AlGaN/GaN’s heterostructure interface is the key to obtaining high-performance nitride sensors. In this paper, we calculated the changes in the density of states and energy bands of the material after AlGaN adsorbed potassium ions through first-principles simulation. Combined with two-dimensional device simulation software, the changes in device performance caused by the changes in material properties are presented. The simulation results show that the adsorption of a single potassium ion can cause a current change in the order of milliamperes, providing a theoretical reference for the subsequent development of high-sensitivity potassium ion sensors.